The Influence of Work Motivation, Work Conflict and Commitment to Employee Performance at PT. XYZ - Sidiq, Ilham; winanti, winanti; Riyanto, Fajar; Natswa, Fida Maulida; Adella, Adella; Nurwati, Mega Indri (Journal of E-business and Management Science, 2024)
This research is motivated by the problem of decreased employee performance at PT XYZ which is influenced by low work motivation, increased work conflict, and lack of employee commitment. This study aims to analyze the effect of work motivation, work conflict, and commitment on employee performance, both partially and simultaneously. A quantitative approach was used with an associative method, involving 60 respondents from the total population of company employees. Data were collected through questionnaires and analyzed using multiple linear regression to measure the relationship between variables. The results showed that partially, work motivation, work conflict, and commitment have a positive and significant influence on employee performance. Simultaneously, the three variables contributed 71.7% to performance, with the rest influenced by other factors outside the study. This study suggests that companies strengthen work motivation through reward programs, manage conflict constructively, and increase commitment through training and supportive policies.